Abdominal breathing manoeuvre reduces passive drag acting on gliding swimmers - Maruyama, Y.; Yanai, T. (Sports Biomechanics, 2015)
The purpose of this study was to test the hypothesis that the passive drag acting on a gliding swimmer is reduced if the swimmer adopts an abdominal breathing manoeuvre (expanding the abdominal wall) rather than chest breathing manoeuvre (expanding the rib cage). Eleven male participants participated in this study. A specialised towing machine was used to tow each participant with tension set at various magnitudes and to record time series data of towing velocity. Participants were asked to inhale air by expanding the abdominal wall or the rib cage and to maintain the same body configuration throughout gliding. The steady-state velocity was measured and the coefficient of drag was calculated for each towing trial to compare between the breathing manoeuvres. The results showed that the towing velocity was increased by 0.02 m/s with a towing force of 34.3 N and by 0.06 m/s with a towing force of 98.1 N. The coefficient of drag was reduced by 5% with the abdominal breathing manoeuvre, which was found to be statistically significant (p < 0.05). These results indicate that adopting the abdominal breathing manoeuvre during gliding reduces the passive drag and the hypothesis was supported.